Relatório de Estágio Profissional "Aprender a Ensinar, Ensinando a Aprender" - Diogo Miguel Costa Monteiro (2017)
The school placement represents one of the most important experiences for any student who aspires the teaching career. In the second year of the Master's degree in Physical Education in primary and secondary education, at Porto's University Sport Faculty, the supervised teaching practice represents a key stage where the Student-Trainee faces reality, experiencing it in the field. The application of the theory in practice causes a series of doubts and questions that during the professional internship are discussed and explored stimulating the development and constant knowledge. This journey ends with the elaboration of the internship report. In this document, the experiences and considerations of the practice teaching are described during the year of the internship in Gaia's College on the academic year of 2016/2017. This document is organized in five chapters: (1) Introduction, which describes the characterization of the Professional Internship and its main purposes; (2) Personal Context where it's exposed a brief presentation of the Student- Trainee, justifying its participation in this stage; (3) Institutional Framework in which it's characterized the environment, context of this year and the internship center and students; (4) Operational Framework, which treats the areas of the Teaching and Learning Organization Management, the Participation in school and the Relation with the coexistence in the work environment; (5) Conclusion, where the Professional Internship is reflected and approached succinctly. Finally, the bibliographical references and the appendixes are presented. KEW-WORDS: